2014
DOI: 10.1016/j.envpol.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two PBDE congeners on the moulting enzymes of the freshwater amphipod Gammarus pulex

Abstract: a b s t r a c tPolybrominated diphenyl ethers (PBDEs) are abundant in aquatic environment. However, only few studies have investigated their impacts on freshwater invertebrates. This work aimed to study the effects of BDE-47 and BDE-99 congeners on the chitobiase and chitinolytic enzymes activities of the freshwater amphipod Gammarus pulex, according to gender, PBDE concentration and time of exposure. In addition, the bioaccumulation of BDE-47 and BDE-99 were measured. Results revealed that females have bioacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…Unfortunately, the release of PBDEs in ecosystems continues due to their presence in products currently in use and new products manufactured using recycled PBDE-containing material (La Guardia et al 2006). It has been shown that PBDEs, especially BDE-47 and BDE-99 congeners, bioaccumulated in several aquatic organisms such as fish or bivalves (Gustafsson et al 1999;Lema et al 2007;, but also amphipod (Tlili et al 2012;Gismondi and Thomé 2014;Lebrun et al 2014). Despite these observations, only few studies have investigated PBDEs toxic effects on invertebrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the release of PBDEs in ecosystems continues due to their presence in products currently in use and new products manufactured using recycled PBDE-containing material (La Guardia et al 2006). It has been shown that PBDEs, especially BDE-47 and BDE-99 congeners, bioaccumulated in several aquatic organisms such as fish or bivalves (Gustafsson et al 1999;Lema et al 2007;, but also amphipod (Tlili et al 2012;Gismondi and Thomé 2014;Lebrun et al 2014). Despite these observations, only few studies have investigated PBDEs toxic effects on invertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…is a suitable organism for ecotoxicological assessment of environmental pollutants at a large scale because they are present in most rivers in Europe (Ja_ zd_ zewski 1980). In addition, many ecotoxicological studies have been conducted with gammarids as model to evaluate pollutants impacts (Leroy et al 2010;Gismondi et al 2013;Gismondi and Thomé 2014;Lebrun et al 2014), and some antitoxic defences have been developed in Gammarus sp. as biomarkers (Geffard et al 2007;Lacaze et al 2011;Sroda and Cossu-Leguille 2011;Gismondi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Snyder and Mulder (2001) have also suggested that the delay in the beginning of molting of larvae in the lobster H. americanus when exposed to heptachlor, probably correlated to a drop in the concentrations of circulating ecdysteroids. Moreover, knowing that crustacean reproduction is linked to the molt cycle (Hyne, 2011), disruption in the molting process could also cause disturbances in reproduction as hypothesized by Gismondi and Thomé (2014) in the amphipod, G. pulex. Indeed, it was observed that the anti-ecdysteroidal activity of nonylphenol caused a reduction in fecundity of many insects (LeBlanc et al, 2000).…”
Section: Chlordecone Effects On the 20-he Concentrationmentioning
confidence: 99%
“…Indeed, Zou and Fingerman (1999c) observed that some estrogenic agents, such as Aroclor 1242, diethylstilbestrol or endosulfan, inhibited chitobiase activity of the crustacean Uca pugilator. Similarly, Gismondi and Thomé (2014) noted that some pollutants, suspected of being EDCs (i.e. polybromodiphenyl ethers), could disturb the chitobiase activity of the amphipod Gammarus pulex.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impacts of endocrine-disrupting compounds (EDCs) on wildlife have focused mainly on hormonal regulation related to reproduction and development processes which have critical roles in population dynamics (Arukwe and Goksøyr 2003;Gismondi and Thomé 2014;Jubeaux et al 2012). Indeed, many pollutants in aquatic environment are able to interfere with the endocrine system of exposed organisms which could lead to dysfunctions of biological processes (e.g., growth, reproduction) (Hyne 2011).…”
Section: Introductionmentioning
confidence: 99%